Enhancing interprofessional ward rounds by identifying factors associated with low satisfaction and efficiency: a quantitative and qualitative national survey of Swiss healthcare professionals (Swiss Medical Weekly, 2025)
AIMS OF THE STUDY: Interprofessional ward rounds are a cornerstone of patient-centred care for medical inpatients and offer opportunities to discuss and coordinate patient treatment and further management. We aimed to identify factors associated with lower satisfaction and efficiency of interprofessional ward rounds, as reported by physicians and nurses.METHODS: An anonymous Swiss nationwide online survey of physicians and nurses was conducted in 28 Swiss internal medicine inpatient departments between 9 August and 19 October 2023. Analyses were conducted from November to December 2023. The primary outcome was physicians’ and nurses’ perceived lower satisfaction with ward rounds, which was assessed using visual analogue scales ranging from 0 to 10, with lower satisfaction defined as scores below the median. The main secondary outcome was perceived lower efficiency using a similar definition. Qualitative analysis was performed through inductive thematic analysis.RESULTS: The survey had a response rate of 21.6% (547/2530). Of the 547 physicians and nurses included in the final analysis, the median satisfaction was 7 points (interquartile range [IQR] 6–8). A total of 61% of physicians (156/254) and 76% of nurses (224/293) reported lower satisfaction. Lower satisfaction was reported significantly more frequently by nurses (adjusted odds ratio [OR] 2.33, 95% confidence interval [CI] 1.58–3.43; p ≤0.001) and female team members (adjusted OR 1.95, 95% CI 1.32–2.9; p